Drying graphene hydrogel fibers for capacitive energy storage. (30th August 2020) - Wang, Chaojun; Zhai, Shengli; Yuan, Ziwen; Chen, Junsheng; Yu, Zixun; Pei, Zengxia; Liu, Fei; Li, Xuezhang; Wei, Li; Chen, Yuan
Abstract: Graphene hydrogel fibers are promising electrode materials for emerging wearable energy storage devices. They shrink significantly (up to 10 times in volume) during drying when trapped solvents are removed, accompanied by complex internal structural transformation. This vital drying process has been ignored in previous research. Here, we present a comprehensive study to correlate the drying of graphene hydrogel fibers with their porous structures and electrochemical properties. Five representative drying conditions involving different temperatures, pressures, and solvent exchanging conditions were compared. We found that first, the average interlayer spacing of stacked graphene nanosheets measured by X-ray diffraction is determined during hydrothermal assembly. During drying, the fast solvent removal causes significant pore closure and creates randomly oriented tortuous pores. On the other hand, the evaporation of solvents provides capillary forces to drive the rearrangement of stacked rGO. Trapping non-volatile solvents in hydrogel rGO fibers can preserve interconnected pores, while freeze-drying leads to non-interconnected pores. Subsequently, different dried graphene fibers have dramatically different specific volumetric capacitance ranging from 5 to 120 F cm −3 and diverse rate capability in capacitive energy storage. These new fundamental insights provide useful guides for controllable assembly of 2D materials into fiber architectures for energy storage applications and beyond. Graphical abstract: Image 1